Peranan Permainan Engklek Terhadap Kecerdasan Logika Matematika Siswa Sekolah Dasar - Cahya Ningrum, Rafika; Arini, Ririn; Nurwati, Agie; Mukti Leksono, Suroso (Universitas PGRI Yogyakarta, 2024)
This research aims to explore and analyze the role of the engklek game on the mathematical logic intelligence of elementary school students. Mathematics education at the elementary school level plays a crucial role in forming the basis for understanding mathematical concepts. Even though many students experience low interest in mathematics, the crank game is identified as an interesting alternative to improve mathematical logic intelligence. The research method used was qualitative with a case study approach at SD Negeri Tunjung Teja 1. Data was collected through observation, interviews and literature study. The research results show that the engklek game not only acts as entertainment but also as a fun learning strategy. From a neuroscience perspective, the activities in this game stimulate the areas of the brain involved in logical and analytical thinking, thereby increasing students' mathematical logic intelligence. This research has positive implications for mathematics learning in elementary schools, creating a fun and interactive learning environment, increasing student motivation and stimulating student cognitive development. Thus, the engklek game is considered an effective tool for improving the quality of mathematics learning in elementary schools.